2021
DOI: 10.1080/14992027.2021.1951853
|View full text |Cite
|
Sign up to set email alerts
|

How do patients decide on interventions for single sided deafness? A qualitative investigation of patient views

Abstract: Background: Single-sided deafness presents communication challenges for adults. There are a range of care options, including CROS hearing aids, available but little is known about patient preferences for these interventions. Objective: The objective of this study was to understand the viewpoints of patients making decisions about audiological interventions they use. Methods: A constructivist worldview using thematic analysis to undertake a constant comparative analysis of 8 semi-structured interviews. Sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…However, in line with previous literature, 17 , 19 we could not identify any patient or disease‐specific characteristics related to the choice of treatment after the trial periods. Similar to other studies, 18 , 19 , 26 the choice of treatment was mainly driven by subjective factors. The described subjective BCD and CROS advantages and disadvantages in our study were comparable to previous literature reporting on reasons for treatment acceptance or rejection.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, in line with previous literature, 17 , 19 we could not identify any patient or disease‐specific characteristics related to the choice of treatment after the trial periods. Similar to other studies, 18 , 19 , 26 the choice of treatment was mainly driven by subjective factors. The described subjective BCD and CROS advantages and disadvantages in our study were comparable to previous literature reporting on reasons for treatment acceptance or rejection.…”
Section: Discussionsupporting
confidence: 57%
“…In literature, reported reasons for treatment acceptance or rejection are diverse and cover objective as well as subjective reasons. The most important reasons for rejection include limited benefit in hearing abilities, physical discomfort, the need for surgery, cosmetic reasons or a better experience with another device 17–19,26 . Currently, there are no clear patient‐ or disease‐specific characteristics identified to be related to the choice of treatment 17,19 …”
Section: Introductionmentioning
confidence: 99%
“…10 Manchester University Hospitals NHS Foundation Trust, Manchester Academic Health Science Centre, Oxford Road, Manchester M13 9WL, UK. 11 Division of Infection, Immunity and Respiratory Medicine, Faculty of Biology, Medicine and Health University of Manchester, Oxford Road, Manchester M13 9PL, UK. 12 National Acoustic Laboratories, Australian Hearing Hub, Macquarie University, Sydney, NSW 2109, Australia.…”
Section: Abbreviationsmentioning
confidence: 99%
“…However, the difficulties that SSD imposes can also affect the individual's psychological and social well-being [8,9], and therefore, outcomes that assess the impact on an individual's overall health and well-being are also relevant and potentially as important [10]. Healthcare users express uncertainty about choice of treatment options for SSD often due to a lack of clarity about their benefit [11]. A subsequent systematic review identified a total of 520 outcome domains from 96 studies that evaluated SSD interventions [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the di culties that SSD imposes can also affect the individual's psychological and social well-being [8,9], and therefore outcomes that assess the impact on an individual's overall health and well-being are also relevant and potentially as important [10]. Healthcare users express uncertainty about choice of treatment options for SSD often due to a lack of clarity about their bene t [11]. A subsequent systematic review identi ed a total of 520 outcome domains from 96 studies that evaluated SSD interventions [12].…”
Section: Introductionmentioning
confidence: 99%